2015
DOI: 10.1007/s11882-015-0518-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Textiles in Dermatitis: An Update

Abstract: Dermatitis has important implications for individuals who are affected. It can significantly impair function and quality of life. Dermatitis is multi-factorial and often includes elements of atopic dermatitis, allergic contact dermatitis, and irritant contact dermatitis in a co-existent manner. Textiles are in contact with the human skin for extended periods of time and as a result, they are an important part of the cutaneous environment. Thus, it is not surprising that textiles play a major role in both the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 50 publications
(45 reference statements)
0
36
0
1
Order By: Relevance
“…Tight skin contact to garments is supposed to increase the risk of the development of contact allergy to textiles . Furthermore, moisture has been reported to facilitate the release from textiles . On the basis of this, patch testing with allergens from textiles and leather is particularly indicated in patients with eczematous lesions in corresponding textile‐covered body regions.…”
Section: Discussionmentioning
confidence: 99%
“…Tight skin contact to garments is supposed to increase the risk of the development of contact allergy to textiles . Furthermore, moisture has been reported to facilitate the release from textiles . On the basis of this, patch testing with allergens from textiles and leather is particularly indicated in patients with eczematous lesions in corresponding textile‐covered body regions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our patient showed positive patch test reactions solely to these textile allergens, and not to the other more commonly reported allergens associated with vulvar contact dermatitis, namely, Myroxylon pereirae (balsam of Peru), fragrance mix, ethylenediamine, neomycin, topical corticosteroids, and caine mix . Moreover, our review of the literature showed that the genitalia and the perianal area are not listed as common sites of textile‐induced dermatitis . In fact, in the the aforementioned studies of vulvovaginal ACD, textile allergen series were not included in patch testing .…”
Section: Discussionmentioning
confidence: 60%
“…Our case exemplifies the importance of considering textiles in clothing as a cause of persistent vulvar and perianal dermatitis, for which the most common allergic culprits are disperse dyes and formaldehyde resins. We note that the rate of true formaldehyde‐associated textile dermatitis is declining in the United States as textiles with lower rates of formaldehyde release are now used, but the presence of cellulosic fibres treated with these resins (especially rayon) within some athletic garments and underwear is possible . Interestingly, our patient showed positive patch test reactions solely to these textile allergens, and not to the other more commonly reported allergens associated with vulvar contact dermatitis, namely, Myroxylon pereirae (balsam of Peru), fragrance mix, ethylenediamine, neomycin, topical corticosteroids, and caine mix .…”
Section: Discussionmentioning
confidence: 69%
“…In patients with AD, direct contact with certain textiles with rigid fibers (e.g. wool or nylon) is a source of irritation [ 242 ], while the use of soft fabrics (e.g. knitted silk; cotton, with or without silver enrichment) may reduce the skin irritation [ 3 , 243 ].…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%